Are neuromodulation interventions associated with changes in the gut microbiota? A systematic review. (1st February 2023) - Korenblik, Vera; Brouwer, Marlies E.; Korosi, Aniko; Denys, Damiaan; Bockting, Claudi L.H.; Brul, Stanley; Lok, Anja
Abstract: The microbiota-gut-brain axis (MGBA) refers to the bidirectional communication between the brain and the gut microbiota and recent studies have linked the MGBA to health and disease. Research has so far investigated this axis mainly from microbiota to brain but less is known about the other direction. One approach to examine the MGBA from brain to microbiota is through understanding if and how neuromodulation might impact microbiota. Neuromodulation encompasses a wide range of stimulation techniques and is used to treat neurological, psychiatric and metabolic disorders, like Parkinson's Disease, depression and obesity. Here, we performed a systematic review to investigate whether neuromodulation is associated with subsequent changes in the gut microbiota. Searches in PsycINFO and MEDLINE were performed up to March 2022. Included studies needed to be clinical or preclinical studies comparing the effects of deep brain stimulation, electroconvulsive therapy, repetitive transcranial magnetic stimulation, transcranial direct current stimulation or vagal nerve stimulation on the gut microbiota before and after treatment or between active and control groups. Seven studies were identified. Neuromodulation was associated with changes in relative bacterial abundances, but not with (changes in) α-diversity or β-diversity. Summarizing, currently reported findings suggest that neuromodulation interventions are associated with moderate changes in the gut microbiome. However, findings remain inconclusive due to the limited number and varying quality of included studies, as well as the large heterogeneity between studies. More research is required to more conclusively establish whether, and if so, via which mechanism(s) of action neuromodulation interventions might influence the gut microbiota. This article is part of the Special Issue on 'Microbiome & the Brain: Mechanisms & Maladies'. Graphical abstract: Image 1 Highlights: The microbiota-gut-brain axis is less-studied in the direction from brain to gut. Investigating the effects of neuromodulation on the gut microbiota is a novel research area. Initial findings suggest that neuromodulation treatment might be associated with changes in bacterial abundances. Future research should study mechanisms underlying the relation between neuromodulation and changes in the gut microbiome.